PENGUATAN KADER PENDAMPING SOSIAL DALAM MENURUNKAN KEJADIAN LOSS TO FOLLOW-UP TERAPI ANTIRETROVIRAL PADA ORANG DENGAN HIV AIDS - Dicky Endrian Kurniawan; Retno Purwandari; Baiq Lily Handayani (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Antiretroviral (ARV) therapy has become the standard of minimal care for people living with HIV. The length of treatment has an impact on the adherence toward ARV consumption. Non-adherence to ARV treatment will result in loss to follow-up and can worsen the condition. Social cadres are active in assisting the government in preventing loss to follow-up. The obstacles they face are the lack of optimal monitoring of ARV consumption and knowledge about ARV. This community service activity aimed to strengthening and optimizing the role of PLWHA social cadres. This activity consists of three stages: (1) focus group discussions with PLWHA mentoring cadres on challenges and problem-solving strategies, (2) drafting guidelines for monitoring ARV consumption for PLWHA that social cadres can use, and (3) training for PLWHA mentoring cadres on mastery of ARV concepts and loss to follow-up prevention management. The activity results show that there is a solution to the problems faced by social cadres in the form of a strategy for monitoring ARV consumption and increasing knowledge of PLWHA about ARV therapy and efforts to reduce the incidence of loss to follow-up. It is hoped that this activity will continue to evaluate the success of this problem-solving strategy and that social cadres can play an active role in reducing the incidence of loss to follow-up.